Activity of upper body muscles in double poling and skierg workout - Horyna, R.; Baèáková, R.; Chrástková, M.; Sedlák, J.; Èmejla, R.; Kraèmar, B. (Baltic Journal of Sport and Health Sciences, 2016)
Background. The aim of the study was to compare the involvement of upper body muscles during double poling and SkiErg Concept 2 workout and verify its specificity for cross-country skiing. Methods. Ten elite Czech cross-country skiers performed double poling and SkiErg workout. Electromyography of selected upper body muscles and cycle characteristics were analysed. To monitor the electrical activity of muscles, we used the device ME6000. Data were analysed using Mega Win and MATLAB software version R2012b. Results. Relative poling phase during double poling was 30.30 ± 2.02% and during SkiErg workout 54 ± 3.36%. Pre-activation of trunk flexors was significantly higher during double poling due to high and forward body position before pole plant. Pre-activation of trunk flexors was not significantly different as pre-activation of shoulder and elbow extensors during SkiErg workout. Deactivation of these muscles came significantly later during SkiErg workout. Conclusion. SkiErg cannot be considered a specific training method for cross-country skiing. It can be recommended to obtain specific power, but long-term application may cause disruption of double poling technique, especially timing of trunk flexors, shoulder and elbow extensors.